The Critical Role of microRNA-21 in Non-alcoholic Fatty Liver Disease Pathogenesis - Liu, Mingjing; Lu, Ting; Bai, Yuanling; Han, Xingyu; Zhang, Wanyi; Zhang, Lei; Chen, Shudan; Lin, Chen; Liu, Chaoqi; Yuan, Chengfu (Current Pharmaceutical Design, 2023)
Nonalcoholic fatty liver disease (NAFLD) has received worldwide scientific attention because of its rapidly increasing prevalence, and it has emerged as a serious public health problem in end-stage liver disease. Many factors are involved in the multifactorial development and progression of liver disease by influencing multiple signaling and metabolic pathways. Currently, many studies have demonstrated the critical role of microRNA- 21 (miR-21) in NAFLD pathogenesis. In addition, many studies have found that miR-21 is highly expressed in inflammatory bowel disease, which is associated with intestinal barrier dysfunction and altered gut microbiota. In this paper, we focus on the regulatory role of miR-21 in the progression of NAFLD and its effect on the gut microbiota, summarize the involvement of miR-21 through a variety of signaling pathways and metabolic pathways, as well as discuss some predicted miR-21 target genes and miR-21 pathways for future experimental identification.
Keywords: microRNAs